The role of urban landscape in the dynamics of islamic education in the archipelago : Theoretical and historical study - Aliwan; Ahmad Mustafidin; Abdul Hakim; Santi Ratnawati; Kunfuaidah Latifah; Arief Hidayatulloh (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The urban landscape plays an important role in the dynamics of Islamic education in the archipelago. As the center of social, economic, and cultural interaction, the urban landscape supports the development of Islamic education institutions, both formal and non-formal. Modernization and urbanization have brought significant changes in the Islamic education system, creating opportunities in expanding access and learning innovation, but also presenting challenges in the form of commercialization of education, degradation of traditional values, and inequality of access. Therefore, this study aims to analyze the relationship between urban landscape and Islamic education from historical and theoretical perspectives, examine the impact of modernization on infrastructure, curriculum, and patterns of social interaction, and formulate strategies for optimizing the urban landscape as a sustainable Islamic education ecosystem. This research uses a qualitative approach with historical, phenomenological, and descriptive-analytical methods. Data were obtained through literature studies, field observations, interviews with academics and Islamic education practitioners, and analysis of relevant policy documents.. The results of the study show that (1) the urban landscape contributes to strengthening Islamic education by accelerating the spread of religious knowledge, expanding the network of ulama, and encouraging innovation in learning methods. (2) urbanization also poses challenges, such as the commercialization of education, shifting cultural values, and inequality of access to Islamic education in urban environments. (3) To overcome these challenges, an adaptive strategy is needed that includes the use of digital technology in learning, strengthening the role of mosques as community-based education centers, and developing Islamic education areas that are integrated with urban spatial planning, Strengthening the Role of Media in Islamic Da'wah and Education With the right strategy, the urban landscape can be optimized as an inclusive Islamic education ecosystem, adaptive to the development of the times, and still maintaining the values of Nusantara Islam.